Functional domains of Acinetobacter bacteriophage tail fibers - Peters, Danielle L.; Gaudreault, Francis; Chen, Wangxue (Frontiers in Microbiology, 2024)
A rapid increase in antimicrobial resistant bacterial infections around the world is causing a global health crisis. The Gram-negative bacterium Acinetobacter baumannii is categorized as a Priority 1 pathogen for R&D of new antibiotics by the World Health Organization due to its numerous intrinsic antibiotic resistance mechanisms and ability to quickly acquire new resistance determinants. Interest in the clinical application of bacteriophages, or their specialized enzymes, to treat A. baumannii infections has been gaining momentum. Specialized phage enzymes, called depolymerases, encoded in the tail fibers of many A. baumannii phages have significant therapeutic potential as novel alternatives to antibiotics and must be further investigated. To this end, the tail fibers of 71 sequenced and fully characterized phages were identified from published literature and analyzed for functional domains associated with depolymerase activity. We found the domains associated with depolymerase function were pectate lyase (SSF51126), Tailspike binding (cd20481), (Trans)glycosidases (SSF51445), and potentially SGNH hydrolases. Identification of the functional domains these specialized enzymes use lays the groundwork to exploit these enzymes for therapeutic purposes in combating the antimicrobial resistance crisis.